Wolfgang Marx (ed.), “I Don't Belong Anywhere”: György Ligeti at 100, (Turnhout: Brepols, 2022). ISBN 9780367339555, 300 pp, £110 (hardback). - Favali, Federico (Journal of the Society for Musicology in Ireland, 2025)
A Review of Wolfgang Marx (ed.), “I Don't Belong Anywhere”: György Ligeti at 100, (Turnhout: Brepols, 2022). ISBN 9780367339555, 300 pp, £110 (hardback).